Larval dispersal and predation in experimental populations of Chrysomya albiceps and Cochliomyia macellaria (Diptera: Calliphoridae) - Andrade, Juliana Bartholo de [UNESP]; Rocha, Fabrícia Aparecida [UNESP]; Rodrigues, Patrícia [UNESP]; Rosa, Gisele Souza [UNESP]; Faria, Lucas Del Bianco [UNESP]; Von Zuben, Claudio José [UNESP]; Rossi, Marcelo Nogueira [UNESP]; Godoy, Wesley Augusto Conde [UNESP] (Instituto Oswaldo Cruz, Ministério da Saúde, 2002)
In this study we investigated the larval dispersal associated with larval predation in experimental populations of Chrysomya albiceps and Cochliomyia macellaria. Frequency distribution of sampling units (G test) in the substrate was used to evaluate variation in larval dispersal. An experimental acrylic channel (1 x 0.1 x 0.2 m) covered with wood shavings was used to observe larval dispersal prior to pupation. The acrylic channel was graduated at 0.05 m intervals, each representing a sampling unit; hence, 20 sampling units were set up. A Petri dish containing third instar larvae of single and double species was deposited at one edge of the acrylic channel allowing larvae to disperse. The number of buried pupae (0, 1, 2, n) present in each sampling unit was recorded. For double species, the number of recovered larvae of C. albiceps was similar to the number initially released on the dish Petri. on the other hand, the number of recovered larvae of C. macellaria was significantly smaller than the initially released number. The results show that C. albiceps attacks C. macellaria larvae during the larval dispersal process. The larval distribution of C. albiceps did not differ significantly from C. macellaria in double species, but it differed significantly in single species. The larval aggregation level of C. macellaria decreased when C. albiceps was present and the larval aggregation level of C. albiceps increased when C. macellaria was present. The implications of such findings for the population dynamics of these species are discussed.
Keywords: larval dispersal; predation; frequency distribution; blowflies